ʺDevelopment of communication competence in higher education students through feedbackʺ - Kharkivska, A.; Shtefan, L. (Problems of Engineer-Pedagogical Education, 2024)
Communication competence is one of the key professional competences that should be developed in modern graduates of higher educational institutions. Feedback is one of the ways to develop communication competence in higher education students. Feedback enables higher education students to realise their own strengths and weaknesses in communication, as well as to receive constructive recommendations for further self-development. The analysis of scientific and pedagogical literature has made it possible to clarify the role of feedback in education in general and in the development of communication skills in particular. The article highlights the factors that should be taken into account when using feedback in the educational process. The ways of effective implementation of feedback, which are the most effective in ensuring the development of communicative competence of higher education students, are proposed. The types of feedback that can be used in the development of future specialists' communicative competence are identified. Among the features of achieving effectiveness from feedback are the following: openness, timeliness, accuracy of opinion, validity, consideration of the situation, and bilateralism. The article emphasises the importance of implementing constructive, so-called "healthy" feedback, which helps to improve mutual understanding, develop relationships and achieve common goals in the educational environment. The most popular digital resources and other tools (methods) of feedback in the development of communicative competence of higher education students are highlighted. The relationship between the development of communicative competence through feedback and self-esteem and self-improvement is traced. Prospect for further research is to study the impact of feedback on the academic achievements of higher education students throughout the entire period of obtaining the relevant degree of education.